Toward a Long‐Term Low Emission Development Strategy: The Case of Energy Transition in Qatar - Fadi Al‐Noaimi (19342861) (2023)
The objective of this paper is to present a comprehensive perspective on the development of a long‐term low‐emission development strategy for Qatar, in line with the Paris Agreement. The methodology used in this paper takes a holistic approach by analyzing national strategies, structures, and mitigation measures from other countries, and synthesizing these with Qatar's unique context in terms of its economy, energy production, and consumption, as well as its energy‐related emission profile and characteristics. The findings of this paper identify key considerations and elements that policymakers would need to take into account when developing a long‐term low‐emission vision for Qatar, with a particular emphasis on its energy sector. The policy implications of this study are significant for policymakers in Qatar, as well as for other countries facing similar challenges in their transition to a sustainable future. This paper contributes to the discourse on energy transition in Qatar and provides insights that can inform the development of potential routes to reduce greenhouse gas emissions in Qatar's energy system. It serves as a foundation for further research and analysis and can contribute to the development of more effective and sustainable policies and strategies for low‐emission development in Qatar and beyond. Other Information Published in: Global Challenges License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/gch2.202200229